Hubungan Motivasi Belajar Terhadap Hasil Belajar Mahasiswa STKIP Budidaya Binjai di Masa Pandemi Covid – 19 - Khairina Afni; Dewi Rulia Sitepu; Mardiati; Lilis Saputri (Jurnal Multidisiplin Madani, 2022)
This study aims to examine the relationship between learning motivation and student learning outcomes at STKIP Cultivation Binjai during the covid-19 pandemic. The type of research used in this research is correlational research. The population of this study were all 35 students in the fifth semester of the Mathematics Education Study Program, STKIP Cultivation of Binjai, with a total sampling technique. The data collection technique used a questionnaire/questionnaire. There is a close relationship between learning motivation and student learning outcomes at STKIP Cultivation Binjai during the Covid-19 Pandemic, which can be seen from the results of student scores relating to learning that are still considered lacking because they still get scores of around 40% and above and some even get a score of 35%. while for the condition of lecturers in teaching, they have received a response of more than 50% and above. This is actually still not enough to increase students' learning motivation. In other words, lecturers have to work harder to increase students' learning motivation so that students get good results in learning.